Re-Thinking Agency (Brill, 2025)
The book explores the multi-faceted nature of contemporary reflections on agency, focusing on various discursive practices that shape the posthumanist approach to the relationship between the human and non-human world from a planetary perspective. The chapters delve into critical human-animal studies, examine new non-anthropocentric identity constructs, and offer analyses that reinterpret meanings through semiotic inversions and challenge static cultural patterns. The book concludes with discussions on decolonization practices that aim to liberate agency from oppressive systems, particularly those dominated by imperial phallogocentrism.